State Responsibility for Fulfilling the Right to Basic Education Facilities Based on Human Rights - Henry Marijes Sopacua (Faculty of Law, Universitas Pekalongan, 2025)
Basic education is a fundamental and non-negotiable human right. This right is universally recognized by various national and international legal instruments, including the 1945 Constitution, ICESCR and CRC. The state has the primary obligation to respect, protect and fulfill the right to basic education, including in terms of providing educational facilities. This study aims to examine the form of state responsibility in fulfilling the right to basic education facilities from a human rights perspective, and to analyze the factors that influence it. The research method used is normative juridical with a qualitative approach to legislation, international legal documents, and academic literature related to human rights and education. The results show that despite the existence of a fairly strong legal framework, the implementation of state responsibility still faces various obstacles. The inhibiting factors include the vagueness of legal norms related to the definition of adequate education facilities, inequality in the distribution of education budgets, geographical challenges in remote areas, local social and cultural values, and weak governance and inter-agency coordination.